Critical discourse analysis on Mandalika and Likupang social media - Sari, Eka Dyah Puspita; Agustina, Mia Fitria; Adiarti, Dian; Hamzah, Rodey Hamza bin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The implications of the pandemic have drastically decreased tourism occupancy in Indonesia, prompting the president to develop super priority destinations, such as Mandalika and Likupang, to restore tourism occupancy. Focusing on Mandalika and Likupang, located in special economic zones, this research aims to critically analyze the social media narratives to uncover the power relations and socio-political constructs embedded in the social media accounts of both destinations. We applied descriptive qualitative research, elaborating the textual elements, discursive, and sociocultural practices of promotional media. The result of the textual elements analysis shows that social media posts mostly use simple sentences, and a deeper lexical analysis reveals that various types of pronouns, adjectives, and collocations are embedded in the posts. Social media leverages persuasive descriptive discourse with friendly, descriptive, and emotional words, improving reader accessibility. Political and cultural narratives also play a significant role in shaping the tourism discourse. Branded as the “New Bali,” Mandalika and Likupang can displace and exclude local culture through social media posts, showing the power of social media in creating tourism discourse. Conclusively, critical discourse analysis helps in understanding the relation between the discourse and the social aspect by analyzing language within a social context.